Analisis Metode Tafsir Al-Marāghī - Ika Parlina; Aam Abdussalam; Tatang Hidayat (ZAD Al-Mufassirin, 2021)
Tafsīr Al-Marāghī  belongs to the group of interpretations that are weighty and high-quality, this can be seen from the writing methods and systematics used by his writing. The purpose of this study was to analyze the method of Tafsir Al-Maragi. Based on the results of the study, Al-Marāghī 's interpretive method suggests verses from the beginning of the discussion, in which case Al-Marāghī  seeks to give only one or two verses that refer to the same meaning and purpose. Explain the vocabulary and syarkh mufradāt that serves to explain words in language, when it turns out that there are words that are difficult for the reader to understand. Explain the meaning of the verse globally. So that the reader does not confuse Al-Marāghī  trying to explain the meaning globally, this effort tries to bridge so that the readers before diving into the deepest meanings can know the meanings of the verse in general.